Language Development Problems Encountered During the Literacy Process in Primary School Students: A Systematic Review of Studies Conducted Between 2016 and 2025 - Zengin, Erdal; Papadakis, Stamatios (Springer, 2026)
This systematic review investigates language development problems encountered by primary school students during the literacy process, based on studies published between 2016 and 2025. Using PRISMA guidelines, 36 empirical studies were selected from major academic databases, including Taylor & Francis, Springer, Elsevier, and ERIC. The analysis focuses on challenges such as phonological awareness deficits, vocabulary limitations, and difficulties in written expression. Findings indicate that these problems are shaped by cognitive, linguistic, socio-cultural, and technological factors. Phonological difficulties were the most frequently reported and were associated with poor reading fluency. Vocabulary problems were prevalent among students from language minority or low socio-economic backgrounds. Issues in written expression were linked to limited exposure to rich linguistic environments and weak instructional strategies. External factors like the COVID-19 pandemic and lack of access to online support further exacerbated learning gaps. Most reviewed studies employed quantitative designs, with limited qualitative insights. The review emphasizes the need for early interventions, phonological training, and vocabulary-enriched instruction tailored to individual needs. These findings inform educators and policymakers aiming to reduce literacy-related inequalities in early primary education.
Keywords: Language development; Early literacy difficulties; Primary school student; Reading and writing skills; Systematic review